Major effect of hydrogen peroxide on bacterioplankton metabolism in the Northeast Atlantic. - Federico Baltar; Thomas Reinthaler; Gerhard J Herndl; Jarone Pinhassi (PLoS ONE)
Reactive oxygen species such as hydrogen peroxide have the potential to alter metabolic rates of marine prokaryotes, ultimately impacting the cycling and bioavailability of nutrients and carbon. We studied the influence of H2O2 on prokaryotic heterotrophic production (PHP) and extracellular enzymatic activities (i.e., β-glucosidase [BGase], leucine aminopeptidase [LAPase] and alkaline phosphatase [APase]) in the subtropical Atlantic. With increasing concentrations of H2O2 in the range of 100-1000 nM, LAPase, APase and BGase were reduced by up to 11, 23 and 62%, respectively, in the different water layers. Incubation experiments with subsurface waters revealed a strong inhibition of all measured enzymatic activities upon H2O2 amendments in the range of 10-500 nM after 24 h. H2O2 additions also reduced prokaryotic heterotrophic production by 36-100% compared to the rapid increases in production rates occurring in the unamended controls. Our results indicate that oxidative stress caused by H2O2 affects prokaryotic growth and hydrolysis of specific components of the organic matter pool. Thus, we suggest that oxidative stress may have important consequences on marine carbon and energy fluxes.